Biofuels in Brazil Fundamental Aspects, Recent Developments, and Future Perspectives - da Silva, Silvio Silvério; Chandel, Anuj Kumar (Springer International Publishing : Imprint: Springer, 2014)
This book discusses the commercialization of biofuels and the Brazilian government policies for the promotion of renewable energy program in Brazil, which could be a learning module for several countries for implementing biofuels policy to improve their socioeconomic status and make them energy independent. Researchers in academia and industries, policy makers, and economic analysts will be assisted by important source of information in their ongoing research and future perspectives. This book will benefit graduate and postgraduate students of chemical and biochemical engineering, forestry, microbiology, biochemistry, biotechnology, applied chemistry, environmental science, sustainable energy, and biotech business disciplines by signifying the applied aspects of bioenergy production from various natural sources and their implications. Graduate and postgraduate students as well as postdoctoral researchers will find clear concepts of feedstock analysis, feedstock degradation, microbial fermentation, genetic engineering, renewable energy generation and storage, climate changes, and techno-economic analysis of biofuels production technologies.